2015
DOI: 10.1007/s40279-015-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Swimming During Childhood and Adolescence on Bone Mineral Density: A Systematic Review and Meta-Analysis

Abstract: While swimming is associated with several health benefits, it does not appear to be an effective sport for improving BMD. Swimmers might be in need of additional osteogenic exercises for increasing BMD values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 57 publications
7
53
1
2
Order By: Relevance
“…It is possible that 24 h may not be sufficiently long to see a significant change in PINP. On the other hand, the absence of a PINP response is in line with the notion that low-impact activities like swimming do not provide sufficient mechanical loading to stimulate bone formation in this age group [10], and this seems to be true irrespective of its high intensity and the supplementation. A previous study in adults reported an immediate increase in PINP following intense running with post-exercise consumption of a protein combined with a carbohydrate beverage [16].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is possible that 24 h may not be sufficiently long to see a significant change in PINP. On the other hand, the absence of a PINP response is in line with the notion that low-impact activities like swimming do not provide sufficient mechanical loading to stimulate bone formation in this age group [10], and this seems to be true irrespective of its high intensity and the supplementation. A previous study in adults reported an immediate increase in PINP following intense running with post-exercise consumption of a protein combined with a carbohydrate beverage [16].…”
Section: Discussionsupporting
confidence: 79%
“…However, the protein requirements for child athletes or highly active children are still unspecified due the lack of studies examining the effects of protein consumption on bone accrual and bone turnover in young athletes, who may have higher needs for protein than non-athletic youth. This may be crucial for young athletes in low-impact sports like swimming who are perceived at an increased risk for suboptimal peak bone mass development because swimming is not an activity typically associated with bonerelated benefits [10]. On the other hand, we recently demonstrated that in adults, low-impact exercise of higher intensity can lead to similar bone metabolism responses as high-impact exercise [11,12], but there is no study of such comparison in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swimming has been shown to have no effect on BMD in a recent meta‐analysis developed in adolescents [4]. Similarly, the effects of swimming on bone structure seem to be neutral, although the literature evaluating bone structure in this population is scarce [3].…”
Section: Introductionmentioning
confidence: 99%
“…Adibidez, luzaroko jarduera aerobiko deritzen ariketek, hala nola igeriketak, bizikletan aritzeak eta ibiltzeak, zenbait seinalek agerian utzi dutenez, nonahiko onurak eragiten dituzte gorputz-sisteman; ez dute, ordea, eragin aipagarririk sustatzen hezurretan [32][33][34]. Hau da, modu erregularrean ibiltzea, adibidez, gaitasun aerobikoan, gantz-metaketan eta zenbait bihotz-faktoreren hobekuntzan mesedegarria den arren, ez da nahikoa hezurren osasuna optimizatzeko.…”
Section: Talkadun Erresistentzia-ariketakunclassified